Polydopamine–cellulose nanofiber composite for flexible electrode material. (12th February 2021) - Muthoka, Ruth M; Roy, Sunanda; Kim, Hyun Chan; Yoon, Hargsoon; Zhai, Lindong; Kim, Jaehwan
Abstract: This research is intended to develop a flexible and dopamine-based electrode material by blending polydopamine (PDA) with cellulose nanofiber (CNF). Inspired by its unique adhesion behavior, dopamine, a biomimetic protein, was utilized to form a strong adhesion between the CNFs. Herein, we report PDA concentration's effect to produce PDA-CNF composite showing good electrochemical redox response, good mechanical properties, and improved thermal stability. The PDA-CNF composite with CNF:PDA = 5:2.5 showed the highest Young's modulus, the strain at break, and toughness among other CNF:PDA combination composites. A PDA-CNF working electrode was made using a microfabrication process. Cyclic voltammetry analysis showed high ion permeability through the CNF backbone structure and oxidation process by PDA in PDA-CNF electrode. These findings indicate the feasibility of the PDA-CNF composite for enhanced longevity in flexible electrode applications utilizing the combination of high mechanical flexibility and thermal stability.